Analisis dan Perancangan Sistem Informasi Manajemen Distribusi Barang Dagang - Taqwiym, Akhsani; Irsyad, Hafiz; Wijaya, Novan (Program Studi Sistem Informasi, Universitas Multi Data Palembang, 2023)
ANH is a business engaged in the distribution of goods with a model of selling and buying goods. The distribution process of goods sold is goods purchased from several suppliers which are then collected and resold. In the process of distributing goods, it is done manually, starting with recording requests to suppliers and customers with note media as proof of transactions. The documentation process for recording proof of transactions often results in documentation errors due to several factors, including, (1) the possibility of adding or reducing ordered products due to changes in orders and not properly documented on notes. (2) the customer contacts ANH again or vice versa to confirm stock availability in the warehouse in real time. Solving problems that occur at ANH can be solved with a good management information system by utilizing technology. The design aimed at solving the problem is to reduce errors in the documentation process by using notes that sometimes change in the field, processing records more quickly and integrated so as to reduce the risk of errors in providing information on goods in the warehouse and errors in the process of inputting purchase requests. The development method used is the iteration method. Analysis of the problems that occur in ANH uses the PIECES (Performance, Information, Economic, Control, Efficiency, Service) framework problem analysis.